(untitled) (Revista Internacional de Folkcomunicação, 2020)
The Covid-19 pandemic scenario stimulated the exposure of musicians in musical lives. Artists who were already present on streaming platforms and on digital social media sought space in order to overcome the requirement of social distance. The article observes the intrinsic relationship between the field of music and the processes of mediatization and proposes to examine how the insertion of regional music from Rio Grande do Sul occurs in some of the broadcasts with the highest audience in the period in streaming. It specifically analyzes the phenomenon of a song recognized as belonging to a specific identity, based on the relationship between lyrics, sounds and rhythm, and its dissemination through memes for deterritorialized audiences. It appears that, from the language of mockery in themes already dealt with by the mythical narrative, the gallant musical aspect assumed in the song expresses contempt for cultured and critical forms of musical expression, and conquers via media both regional audiences and national regionalist niches. Its success expresses the cathartic search for overcoming social asphyxia determined by the context of the pandemic. Mediatization; Gaúcha Pop Music; Pop Music; Grotesque.